Applications of the Numerov method to simple quantum systems using Python - Caruso,Francisco (2022)
Numerov’s numerical method is developed in a didactic way by using Python in its Jupyter Notebook version 6.0.3 for three different quantum physical systems: the hydrogen atom, a molecule governed by the Morse potential and a quantum dot. After a brief introduction to the Numerov method, the complete code to calculate the eigenfunctions and eigenvalues of the hydrogen atom is presented. The necessary code changes to compute the other two examples are also provided in the sequel.